2018
DOI: 10.4236/jtst.2018.43006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Water Repellent Finishes on Cotton Double Jersey Fabrics

Abstract: This study demonstrated that the variation in physical and chemical performance on cotton double jersey knit fabrics was decided by the knit structure, water repellent chemicals types and their concentration. Here, two types of double jersey fabrics were treated with different types of water repellent chemicals at different formulations to evaluate the performance of water repellent finishes on knit fabrics properties. The levels of water repellency of the fabrics were assessed by AATCC 127 hydrostatic head te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The EPA recognizes the importance of fluorochemicals (FC) and their broad range of applications. Thus, the EPA has not banned the use of fluoro-chemicals altogether but only the long-chain (≥C 8 ) FCs that lead to persistent, bio-accumulative, and toxic (PBT) substances found in the food chain, human blood, and the environment [15]. The shorter chain fluorochemicals (≤C 6 ) are less toxic and less bioaccumulative in wildlife and humans [16].…”
Section: Toxicology Of Fluorochemical Finishesmentioning
confidence: 99%
See 2 more Smart Citations
“…The EPA recognizes the importance of fluorochemicals (FC) and their broad range of applications. Thus, the EPA has not banned the use of fluoro-chemicals altogether but only the long-chain (≥C 8 ) FCs that lead to persistent, bio-accumulative, and toxic (PBT) substances found in the food chain, human blood, and the environment [15]. The shorter chain fluorochemicals (≤C 6 ) are less toxic and less bioaccumulative in wildlife and humans [16].…”
Section: Toxicology Of Fluorochemical Finishesmentioning
confidence: 99%
“…Fluoro-chemical treatment significantly changes the mechanical properties of the treated fabric [2]. Some of the undesirable effects of the finish are static electricity build-up, poor soil removal in aqueous laundering, added fabric stiffness, soil redeposition in laundering, loss in tensile strength, and increased flammability [2,15,16]. On the other hand, some of the mechanical properties that are often improved with the finish application include better durable press property, less drying time, more rapid ironing, and improved resistance to certain chemicals.…”
Section: Uses Of Fluorochemical Urethane and Its Impact On Textile Prmentioning
confidence: 99%
See 1 more Smart Citation
“…This repellency can be achieved by applying water repellent chemicals which imparts a thin surface layer of chemicals on textile fibers by the modification of surface energy of textiles without much deterioration of other mechanical and aesthetic properties like strength, flexibility, luster, breathability, softness etc. (Chowdhury & Kawser Parveen, 2018) The formation of permanent covalent bonds between the fiber and water repellent chemicals are necessary to produce durable repellency as the bonds prevents the removal of the water repellent chemicals during laundering or dry-cleaning. Pyridinium compounds, chromium based metal complexes and N-methylol based products accomplish the durable chemical bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the tested materials are primarily used for the production of swimwear, the printed samples are subjected to exposure to the chlorinated water (pool water). In previous studies, several authors exposed samples to different concentrations of chlorine (Epps, 1987;Siddiqua et al, 2017;Chowdhury, 2018) in order to establish the durability of colouration, both dyed and printed textile materials. It has been found that this parameter has an influence on colour fastness and that it depends on the type of ink and pigment, the printing process, the chlorine concentration and the type of material.…”
Section: Introductionmentioning
confidence: 99%